2019
DOI: 10.14710/jitaa.44.1.77-83
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional comparison between dried and ensiled indigofera, papaya and moringa leaves

Abstract: The objective of this experiment was to evaluate chemical composition, in vitro fermentation and digestibility of dried and ensiled indigofera, papaya and moringa leaves. The leaves were subjected to artificial drying in an oven at 60oC for 24 h and ensiling treatment for 30 d under room temperature. Dried and ensiled samples were determined for chemical composition, silage fermentation characteristics and in vitro rumen fermentation and digestibility. The experimental design was a factorial design 3 × 2 in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, such high protein silages have a problem with regard to massive protein degradation and amino acids deamination during the ensiling process [6,7]. Our previous study showed that Indigofera and Moringa leaf silages had high pH values and high ammonia concentrations that contributed to their low silage quality [8]. It had been recommended that a certain silage additive is necessary to prevent or to minimize such considerable proteolysis in high protein silages.…”
Section: Introductionmentioning
confidence: 99%
“…However, such high protein silages have a problem with regard to massive protein degradation and amino acids deamination during the ensiling process [6,7]. Our previous study showed that Indigofera and Moringa leaf silages had high pH values and high ammonia concentrations that contributed to their low silage quality [8]. It had been recommended that a certain silage additive is necessary to prevent or to minimize such considerable proteolysis in high protein silages.…”
Section: Introductionmentioning
confidence: 99%